Effects of El Niño and La Niña events on the sex ratio of southern elephant seals at King George Island - Vergani, D.F. (2004)
The response of altered sex ratio in southern elephant seals due to environmental stress was analysed. Data were collected at King George Island from 1980 to 1994. Significant retreats in the ice cover during El Niño events strongly suggest environmental stress during this period along the Bellingshausen Sea, a zone where female elephant seals from King George Island feed during their pregnancy. Randomly chosen weaning elephant seal pups (n = 1178) were sexed at Stranger Point (King George Island, 62° 14' S, 58° 30' W) over 5 km of beach from 1985 to 1994. Adult sex ratio was also determined annually from 1980 to 1994 as the ratio between maximum number of bulls and females on land. The theoretical pup sex ratio was assumed as 1:1 according to background information. Adult sex ratio was calculated as 1:6. To define the occurrence of El Niño Southern Oscillation (ENSO) during the study period, a sea surface temperature (SST) index called 'Niño 3.4' for the region 5°N to 5° S, 120° E to 170° W was considered. Monthly SST anomalies were obtained from the Climate Prediction Center (CPC, NOAA). To provide an annual index of anomaly strength (IAS), the monthly adjusted oscillation index climatology (AOIC) was averaged. Accumulated values during the whole study period showed that during El Niño years (1987, 1991, 1992) the proportion of pups was significantly biased in favour of females (p < 0.01). During normal years (1986, 1990, 1993, 1994) and La Niña years (1985, 1988, 1989), accumulative values showed a greater proportion of male pups to females (p < 0.05), Using the 1:1 hypothesis, we found during El Niño years a 9% reduction in the male segment, whereas in non-El Niño years a recovery of 7 % was observed (3 % during normal years and 4 % during La Niña years. To see the influence of accumulative values of pup sex ratio in adult sex ratio, a theoretical adult proportion was calculated as 1:6. To test this hypothesis, information on adult sex ratio taken from King George Island between 1980 and 1994 (n = 14 yr) was analysed. The average adult sex ratio for King George Island was 1:7. This value seems to confirm the hypothesis that this population has had a balanced production of male and female pups in the long term. Comparisons with Pacific and Indian declining seal populations were made.